Performance parameter of WiMAX: a study of physical layer of WiMAX under different path loss and modulation techniques / Irmalina Othman - Othman, Irmalina (2013)
WiMAX technology is becoming imperative in modern wireless commnication system nowadays. WiMAX is one of the alternative for users to overcome the limitations of the existing wireless communication such as lack of security, coverage area and low data rate.